2016
DOI: 10.1038/srep37677
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive Toxicity of CdSe/ZnS Quantum Dots on the in vivo Ovarian Function and in vitro Fertilization

Abstract: Despite the usefulness of quantum dots (QDs) in biomedicine and optoelectronics, their toxicity risks remain a major obstacle for clinical usages. Hence, we studied the reproductive toxicity of CdSe/ZnS QDs on two aspects, (i) in vivo ovarian functions and (ii) in vitro fertilization process. The body weight, estrous cycles, biodistribution of QDs, and oocyte maturation are evaluated on female mice treated with QDs. The mRNA level of the follicle-stimulating hormone receptor (FSHr) and luteinizing hormone rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…As cadmium (Cd) and selenium (Se) based QDs are toxic to several cell types the stability of the hydrophilic ligands around the QDs is essential . If the outer hydrophilic shells of the QDs are not stable it will release toxic ions from the core.…”
Section: Resultsmentioning
confidence: 99%
“…As cadmium (Cd) and selenium (Se) based QDs are toxic to several cell types the stability of the hydrophilic ligands around the QDs is essential . If the outer hydrophilic shells of the QDs are not stable it will release toxic ions from the core.…”
Section: Resultsmentioning
confidence: 99%
“…Pu et al reported that the exposure of 15 and 45 mg/Kg Ni nanoparticle to female rat apparently caused the increasing of luteinizing hormone (LH) and follicle stimulating hormone (FSH) and lowered the estradiol (E2) serum levels 30 . In addition, Xu et al found that intravenously injecting CdSe/ZnS QDs into female mice caused apparent reducing of oocyte maturation rate 18 . In this study, the average ovary index of 25.0 μg, 12.5 μg and untreated group were 0.0541±0.0088%, 0.0565±0.0139% and 0.0606±0.0057% and showed no significant difference among 3 groups (Figure 5 A), which meant that the injection of Pdots did not cause the weight change of the maternal ovary.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of titanium dioxide nanoparticles during the placental period caused the pregnancy complication of maternal mouse 32 and altered the brain development related gene expression in fetus 33 . Our previous work discovered that intravenously exposure of CdSe/ZnS QDs to female mice caused the reducing of oocyte maturation rate 18 . For Pdots, there was still rare in vivo toxicity study in this part.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the in vitro fertilization success rate was reduced. [111] Primates intravenously injected with phospholipid micelle-encapsulated CdSe/CdS/ZnS QD (25 mg/kg) showed neither acute nor chronic toxic effects, but they did observe significant accumulation in the liver, spleen and kidneys. A slow degradation of the QD and subsequent release and accumulation of Cd ions was observed in the liver and the spleen.…”
Section: Quantum Dot Solar Cellsmentioning
confidence: 95%